2015
DOI: 10.1002/ajim.22511
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of pneumoconiosis mortality in Kentucky: Analysis of death certificate data

Abstract: Coal worker environmental exposure protection should be enhanced and pneumoconiosis surveillance improvements, including enhanced management of comorbid conditions like COPD, should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Cardiovascular diseases (i.e., atherosclerotic heart disease; acute myocardial infarction, unspecified; congestive heart failure; stroke, not specified as hemorrhage or infarction; and atherosclerotic cardiovascular disease, so described) were among the top ten most common underlying causes of death. Cardiovascular causes of death were also reported among Kentucky residents with pneumoconiosis listed as a cause of death, and another study of coal miners reported an increased risk of ischemic heart disease mortality with coal dust exposure 17,18 . While cardiovascular diseases could be associated with systemic gas exchange abnormalities in coal miners, cardiovascular comorbidities are prevalent in coal miners 16–20 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cardiovascular diseases (i.e., atherosclerotic heart disease; acute myocardial infarction, unspecified; congestive heart failure; stroke, not specified as hemorrhage or infarction; and atherosclerotic cardiovascular disease, so described) were among the top ten most common underlying causes of death. Cardiovascular causes of death were also reported among Kentucky residents with pneumoconiosis listed as a cause of death, and another study of coal miners reported an increased risk of ischemic heart disease mortality with coal dust exposure 17,18 . While cardiovascular diseases could be associated with systemic gas exchange abnormalities in coal miners, cardiovascular comorbidities are prevalent in coal miners 16–20 .…”
Section: Discussionmentioning
confidence: 97%
“…Cardiovascular causes of death were also reported among Kentucky residents with pneumoconiosis listed as a cause of death, and another study of coal miners reported an increased risk of ischemic heart disease mortality with coal dust exposure 17,18 . While cardiovascular diseases could be associated with systemic gas exchange abnormalities in coal miners, cardiovascular comorbidities are prevalent in coal miners 16–20 . Miners participating in the National Institute for Occupational Safety and Health Coal Workers' Health Surveillance Program have a high prevalence of hypertension and obesity, which may or may not be related to mining 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Three studies from the USA reported steadily declining CWP mortality rates among the general population over recent decades both nationally [ 42 – 44 ] and in the Central Appalachian region [ 43 ] with similar patterns also found in Australia [ 56 ]. Only one study looked at survival and found that 80 out of 459 CWP cases without tuberculosis diagnosed from 1963–2014 in a state-owned mine in China had died over the study period [ 49 ], corresponding to a mortality rate of 17.4%.…”
Section: Resultsmentioning
confidence: 69%
“…There was limited information on global mortality for CMDLD. Reductions in CWP mortality rates were reported in the USA and Australia [ 42 – 44 , 56 ], however these are in terms of mortality among the whole population, rather than specifically coal miners. This decreasing trend in CMDLD mortality at a population level was also observed in the Central Appalachian states (USA) despite the increase in CWP prevalence over recent years [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study found pneumoconiosis mortality rates decreased in West Virginia, Pennsylvania, Kentucky, and the USA during 2003-2013. [59] Although increasing prevalence of pneumoconiosis (including CWP) morbidity and declining mortality rates seem paradoxical, there are reasons why they might differ. Individuals can live for many years after a pneumoconiosis diagnosis, so recent cases may not contribute substantially to mortality statistics.…”
Section: Mortality Studiesmentioning
confidence: 99%